THE IMPACT OF INSTRUCTIONAL INTERVENTION ON STUDENTS’ READING COMPREHENSION WITH ANALYTICAL EXPOSITION TEXT - Syam, Sukma Pebriani; AM, St. Asriati; Daddi, Herlina (English Language Teaching Methodology, 2024)
This research aimed to find out the impact of instructional intervention on students' reading comprehension with analytical exposition text. The instrument of this research used a test about analytical exposition text that consisted of 20 question of multiple choice. This research used pre- experimental research that consist of pre-test, treatment and post-test. The sample of this research was class XI of SMA Muhammadiyah 2 Makassar that consisted of 20 students. The sample used a total sampling technique. The data was analyzed using SPSS 29.00. The results of this research showed that the score of pre-test was 28.5 classified as very poor categorized and post-test was 62.5 classified as fair categorized. This research also showed the value of t-test was higher than the value of t- table (T-test > T-table). The value of t-test was 13.309 and the value of t-table was 2.093. It means the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Based on the research results, the researcher concluded that the implementation of an instructional intervention was effective to improve students’ reading comprehension